A Final Result on the Oscillation of Solutions of the Linear Discrete Delayed Equation Δx(n)=−p(n)x(n−k) with a Positive Coefficient. (5th September 2011) - Baštinec, J.; Berezansky, L.; Diblík, J.; Šmarda, Z.
Abstract : A linear( k + 1 ) th-order discrete delayed equationΔ x ( n ) = − p ( n ) x ( n − k ) wherep ( n ) a positive sequence is considered forn → ∞ . This equation is known to have a positive solution if the sequencep ( n ) satisfies an inequality. Our aim is to show that, in the case of the opposite inequality forp ( n ), all solutions of the equation considered are oscillating forn → ∞ .